Forage yield, competition, and economic indices of oat and common vetch intercrops in a semi-arid region - Jiao, Yu; Zhang, Qingping; Miao, Fuhong (Frontiers in Sustainable Food Systems, 2024)
Intercropping of annual favorable legumes with grains to produce forage is utilized extensively worldwide to improve resource use efficiency. To identify the best intercropping system for a semiarid region of China, intercrops of oat (Avena sativa L.) and common vetch (Vicia sativa L.) at five planting proportions and oat and common vetch monocrops were produced over the 2011 and 2012 growing seasons in Xifeng, northwest China. Several indices were used to evaluate yields, competitive interrelationships between the two crops, and economic returns. The oat mono-crop had the highest dry matter yield (6.51 t ha -1 ), while the oat-common vetch intercrop, with an 80:20 planting ratio, produced the highest crude protein production (696 kg ha -1 ). The land equivalent ratio(1.167), relative crowding coefficient(2.445), and actual yield loss(0.750) were more favorable for the oat-common vetch intercrop at a seeding ratio of 20:80. The oat-common vetch intercrop at a seeding ratio of 20:80 showed the highest values for monetary advantage index(35.51). Overall, the autumn-sown 20:80 oat-common vetch intercrop was more productive from resource utilization and economic perspectives.